2020
DOI: 10.1097/anc.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Neonatal Sepsis Calculator in Early-Onset Sepsis and Maternal Chorioamnionitis

Abstract: Background: Utilization of the neonatal sepsis calculator published by Kaiser Permanente is rapidly increasing. This freely available online tool can be used in assessment of early-onset sepsis (EOS) in newborns 34 weeks' gestation or more based on maternal risk factors and neonatal examination. However, many hospitals lack standard guidelines for its use, leading to provider discomfort with practice change. Purpose: The goal of this project was to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…The risk of sepsis per 1000/live births is further quantified with consideration of the infant’s clinical condition after birth, classified as well appearing, equivocal or clinical illness 18 19. Multiple studies have confirmed that implementation of the sepsis calculator has significantly decreased lab sampling and antibiotic use in low-risk infants without adverse outcomes 20–23…”
Section: Introductionmentioning
confidence: 99%
“…The risk of sepsis per 1000/live births is further quantified with consideration of the infant’s clinical condition after birth, classified as well appearing, equivocal or clinical illness 18 19. Multiple studies have confirmed that implementation of the sepsis calculator has significantly decreased lab sampling and antibiotic use in low-risk infants without adverse outcomes 20–23…”
Section: Introductionmentioning
confidence: 99%
“…Arora et al 6 reported a significant reduction in sepsis evaluations (from 90.9% to 68.8%) and a reduction in antibiotic therapy by 29.4% in infants ≥34 weeks' gestation admitted to the NICU. Akangire et al 16 showed a decrease of blood cultures from 14.8% to 7.6%, and a reduction of empirical antibiotic administration from 11% to 5% in neonates at 34 weeks' gestation or more. Implementation of the EOS calculator decreased unnecessary painful procedures, while NICU admissions enabled healthyappearing infants to remain in the newborn nursery with their mothers, and as such promoted bonding.…”
Section: Discussionmentioning
confidence: 98%
“…Still, the postnatal categorization into clinical illness or equivocal group based on the clinical assessment could result in falsely elevated EOS risk as the definitions of equivocal or symptomatic are vague and nonspecific. For instance, Akangire et al 30 found that infants with small pneumothoraces and mild pulmonary hypertension were misclassified as symptomatic infants. Also, the threshold to intervene in symptomatic newborn infants may vary among practitioners.…”
Section: Discussionmentioning
confidence: 99%